2014
DOI: 10.1097/sle.0b013e31828f6721
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Arteriovenous Fistula Formation After En Bloc Stapling of the Renal Hilum During Transperitoneal Laparoscopic Nephrectomies

Abstract: Our aim was to evaluate the risk of arteriovenous fistula (AVF) formation after en bloc stapling of the renal hilum during transperitoneal laparoscopic nephrectomies (LNs). A retrospective review of 35 laparoscopic simple or radical nephrectomies or LNs was carried out. Patients were clinically followed up for renal hilar AVF formation, which could lead to new onset diastolic hypertension, abdominal murmur, and congestive heart failure. In addition, abdominal computed tomography and arteriography were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…[ 4 ] On the other hand, even with separate ligation of the artery and vein, AVF could be a result of inflammation and adhesion. [ 5 ] The most extensive series of AVF research was conducted by Lacombe, where he reported 62 cases of AVF following nephrectomy. However, this mode of ligation was available only for 14 of the 62 patients, 12 of whom successfully underwent en bloc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 4 ] On the other hand, even with separate ligation of the artery and vein, AVF could be a result of inflammation and adhesion. [ 5 ] The most extensive series of AVF research was conducted by Lacombe, where he reported 62 cases of AVF following nephrectomy. However, this mode of ligation was available only for 14 of the 62 patients, 12 of whom successfully underwent en bloc.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, en bloc ligation was assumed to be the reason for AVF, even though 48 patients in the cohort did not undergo this mode of ligation. [ 1 2 4 5 6 ] In our series 91 out of 126 patients were followed up either by CT with contrast or MRI depending on renal function tests. 71 patients for oncological purpose, 20 patients with benign causes where followed up for different indication such as evaluation of renal bed and contralateral kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation